The Effectiveness of Nanotechnology in Sustainable Development - Abdalqadir , Narmeen Abdalwahhab (PROSPECTIVE RESEARCHES, 2025)
Nanotechnology is one of the latest technological and scientific developments in recent years. It is the second industrial revolution that will contribute to achieving the economic, environmental and social dimensions of sustainable development by reducing industrial waste and then eliminating industrial pollution and improving the efficiency of using available economic resources and areas of application. From this standpoint, the research aimed to define nanotechnology and its nature in the industrial sector in general and the Iraqi sector in particular and to show the extent of the possibility of benefiting from it in supporting and achieving the economic, environmental and social dimensions of sustainable development. At the end of the research, the researchers reached a set of conclusions, the most prominent of which is that nanotechnology is an entry point to achieving sustainable development by reducing the resources consumed.